2012
DOI: 10.1007/s10144-012-0305-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevational gradient in the cyclicity of a forest‐defoliating insect

Abstract: Observed changes in the cyclicity of herbivore populations along latitudinal gradients and the hypothesis that shifts in the importance of generalist versus specialist predators explain such gradients has long been a matter of intense interest. In contrast, elevational gradients in population cyclicity are largely unexplored. We quantified the cyclicity of gypsy moth populations along an elevational gradient by applying wavelet analysis to spatially referenced 31-year records of defoliation. Based on geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Moreover, determining invasion rates from a field measurement of population size, as we have done, provides a more accurate picture of spread dynamics than county quarantine records that are coarser in spatial scale and most importantly cannot show retraction of range boundaries. Prior research has demonstrated spatial (Haynes et al 2009(Haynes et al , 2012(Haynes et al , 2013 and temporal (Allstadt et al 2013) variation in the periodic behavior of gypsy moth population dynamics, so the dynamics in the time period and area studied here may differ from the overall, spatiotemporally averaged dynamics of the system. These prior studies of gypsy moth population cycles have focused on New England, New York, and Pennsylvania (where gypsy moth has been established longer, leaving a longer record for analysis), whereas our analysis focused on Virginia and West Virginia given our interest in linking defoliation to spatially detailed trapping records that quantify spread dynamics.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, determining invasion rates from a field measurement of population size, as we have done, provides a more accurate picture of spread dynamics than county quarantine records that are coarser in spatial scale and most importantly cannot show retraction of range boundaries. Prior research has demonstrated spatial (Haynes et al 2009(Haynes et al , 2012(Haynes et al , 2013 and temporal (Allstadt et al 2013) variation in the periodic behavior of gypsy moth population dynamics, so the dynamics in the time period and area studied here may differ from the overall, spatiotemporally averaged dynamics of the system. These prior studies of gypsy moth population cycles have focused on New England, New York, and Pennsylvania (where gypsy moth has been established longer, leaving a longer record for analysis), whereas our analysis focused on Virginia and West Virginia given our interest in linking defoliation to spatially detailed trapping records that quantify spread dynamics.…”
Section: Discussionmentioning
confidence: 92%
“…The modifications accord with the timing of these mortality sources in field populations. Prior studies have shown the model produces an Allee effect at low densities (Bjørnstad et al ) and periodic fluctuations in gypsy moth density across 4 orders of magnitude (Dwyer et al , Bjørnstad et al , Haynes et al ) as observed in field populations of the gypsy moth (Berryman ).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been found that such measurements of area damaged correlates well with measures of population abundance (e.g., light trap data) and can therefore can be used as proxies for population density (Leskó, Szentkirályi, & Kádár, , , ). Furthermore, area of defoliation is a commonly used metric used in analyses of large‐scale population dynamics and spatial synchrony (e.g., Allstadt, Haynes, Liebhold, & Johnson, ; Haynes, Liebhold, & Johnson, ; Liebhold et al., ; Williams & Liebhold, ).…”
Section: Methodsmentioning
confidence: 99%
“…For previous work on discrete time models for gypsy moth population without spatial features, see [12,10,11,5,23].…”
mentioning
confidence: 99%